Segregated Work or Very Minimal Community Employment for Job Workers with Disabilities. (2nd January 2023) - Osegueda, Gavin Ryan
Abstract: In comparison to work centers, supported employment is the more favorable method to advance people with disabilities into the workforce. One of the central goals of the Workforce Innovation and Opportunity Act is to increase supported employment and community job opportunities for people with disabilities by phasing out 14 (c) certificates. Work centers use such certificates to pay people subminimum wages; without a 14 (c) certificate, work centers will close. Though supported employment creates equitable opportunities for job seekers with disabilities, such opportunities are undesirable for some. To emphasize this, the author interprets quantitative data pertaining to job seekers/workers in Walla Walla County, Washington. Walla Walla County, located in rural southeastern Washington, is home to approximately 60, 760 residents. While the majority of those within this study's sample hold community jobs, they, on average, are employed for less than half of the hours they prefer to work. To understand how these limited weekly hour schedules are created, an employment consultant's role is considered in great detail. While workforce inclusion is an unquestionably necessary goal for people with disabilities, their vocational preferences should not be secondary to the possible benefits of community employment.